Platons Demokratiekapitel (Pl. Rep. 555 b 4 – 562 a 3) und das sokratische Argument - Blößner, Norbert (Hyperboreus, 2015)
Plato’s well-known treatment of democracy in Rep. 555 b – 562 a, though often taken to be a statement of Plato’s own political views or his contribution to a debate about constitutions, appears in a very different light if one comes to it with a clear understanding of the term ‘democracy’ and reads the passage within its own context. In that case it comes to be seen as an integral part of Socrates’s project to ascertain the value of justice, and thereby truly to achieve what Socrates had announced it would do in 543 c – 545 c.